CHANGES IN EMISSION SPECTRA DURING CRACK DEVELOPMENT AND ROCK FAILURE - Robsman V.A.; Nikogosyan G.N. (My University, 1989)
Experimental studies of crack generation in rocks by recording of the acoustic and electromagnetic pulses emitted by defects have established general patterns of change in the amplitude and frequency spectra of such acoustic and electromagnetic pulses. As defects accumulate in rocks, the stages of deformation and failure are represented by a sequence of changes of state, with each state having a particular frequency spectrum and a particular distribution of acoustic and electromagnetic energy. The transition from one stage to the next is identified by a abrupt change in the spectral distribution of the signals.